Case report: Multiple cryotherapy sessions in localized Darier's disease: a rare clinical presentation and literature review - Lyu, Yansi; Wang, Bin; Guan, Lyuxin; Ma, Li; Li, Hao (Frontiers in Medicine, 2025)
Darier's disease (DD), a rare hereditary acantholytic dermatosis with high penetrance but variable expressivity, has about 10% of its cases presenting as localized lesions, known as Localized Darier's Disease (LDD). To date, only a very small number of non-segmental LDD cases have been reported. This study reports a case of a 27-year-old Chinese male with LDD, who presented with yellow-brown papules and plaques on the inner side of the right thigh for 1 month. The diagnosis of localized keratosis follicularis was confirmed through dermatoscopic examination and histopathological assessment of the skin lesion. After repeated applications of cryotherapy combined with the use of emollients, while avoiding physical friction and sun exposure, the rash gradually subsided. The patient experienced no adverse reactions after treatment. The occurrence of LDD on the inner thigh, a relatively rare site, provides new insights into the affected areas of LDD, further expands the clinical manifestations of the disease, and offers valuable experience for clinicians in recognizing and managing LDD at different sites, aiding in the optimization of diagnostic and therapeutic strategies.